Mycobacterium leprae BACILLEMIA IN BOTH TWINS, BUT ONLY MANIFEST AS LEPROSY IN ONE SIBLING - Sukmawati, Netty; Agusni, Indropo; Listiawan, M. Yulianto; Prakoeswa, Cita Rosita S.; Adriaty, Dinar; Wahyuni, Ratna; Iswahyudi, Iswahyudi (Institute of Topical Disease Universitas Airlangga, 2016)
Leprosy in twins is rarely reported. A 19 years-old male student, from Lamongan district, was diagnosed as Multibacillary (MB) leprosy in the Skin and STD Clinic of Dr. Soetomo General Hospital Surabaya. Multiple anesthetic skin lesions were found, but the bacteriologic examination was negative for Acid Fast Bacilli (AFB). Histopathology examination support the diagnosis of BL type of leprosy. His twin brother that has been lived together since born until present seems healthy without any complaints of skin lesions and have no signs of leprosy. When a serologic examination for leprosy was performed, a high anti PGL-1 antibody level was found in patient (IgM anti PGL-1 2937 and IgG anti PGL-1 3080 unit/ml) while his healthy twin brother showed only low level (IgM 745 and IgG 0 unit/ml). Interestingly when a PCR study was performed to detect M.leprae in the blood, both of them showed positive results. Using the TTC method, a genomic study of for M.leprae, it is revealed that both samples were identic ( 27x TTC repeats). According to patient's history, he had a traffic accident and got a wound in the knee seven years ago, while the skin lesions seems started from this area around three years ago before it spread to other parts of the body. The patient was treated with Multi-drug therapy (MDT) while his sibling got a prophylactic treatment for leprosy. After 6 months of treatment, the leprosy skin lesions were diminished and the serologic anti PGL 1 has been decreased. His healthy brother also showed a decrease in anti PGL 1 level and no skin signs of leprosy.